Reproductive performance of red-winged tinamous (Rhynchotus rufescens) using different mating strategies in captivity – case report - Correia, L. E. C. S. [UNESP]; Vilar, C. S. M. M.; Martins, E. H. [UNESP]; Oliveira, M. H.V. [UNESP]; Silva, K. M. [UNESP]; Dominguez-Castaño, P. [UNESP]; Mamani, P. M. [UNESP]; Souza, F. F. [UNESP]; Silva, J. A.V. [UNESP] (FapUNIFESP (SciELO), 2022)
The aim of this study was to evaluate the reproductive performance of red-winged tinamous in captivity using different mating systems during three breeding seasons. The data were collected from August to March during three breeding seasons of the species. Ten couples and four groups of red-winged tinamous were randomly selected for formation of the monogamous and polygynous mating system, respectively, with egg collection from both systems. The traits evaluated were number of eggs per female, egg breaking and egg fertilization. Data were statistically analyzed by the least square method and logistic regression. Animals in couples mating strategy were superior (P<0.05) in terms of number of eggs per female compared to the group mating strategy. High egg breaking rate (P<0.05) in the red-winged tinamous groups was observed. Eggs of animals in couples mating strategy were 5.24 and 11.5 more likely to be fertilized than those of group strategy in two breeding seasons. In general, the reproductive efficiency in terms of low egg breaking, high egg production and fertility was observed for red-winged tinamous from the monogamous mating system.
Desempenho reprodutivo de perdizes (Rhynchotus rufescens) utilizando diferentes estratégias de acasalamento em cativeiro – relato de caso
Keywords: Egg-laying; Fertility; Monogamy; Tinamidae